Conventional and unconventional treatments for migraine - Mielniczek, Katarzyna; Dołomisiewicz, Diana; Dalmata, Weronika; Gąbka, Ilona; Dąbrowski, Jan (Journal of Education, Health and Sport, 2023)
Migraine is one of the leading causes of disability in humans. It causes significant deterioration in patients' lives and prevents daily functioning. Its main symptoms include photophobia, an enormous stabbing headache, nausea and vomiting. In addition, it can be accompanied by tinnitus, visual disturbances or dizziness. Before diagnosing migraine, serious intracranial pathology or other neurological conditions should be ruled out. Treatment of acute migraine is difficult due to significant rates of nonresponse to medications and the difficulty in predicting individual response to a particular agent or dose. A new class of drugs, calcitonin gene-related peptide (CGRP) antagonists, has been approved for the prevention of migraine in adults. In contrast, effective first-line therapies for mild to moderate migraine are over-the-counter nonsteroidal anti-inflammatory drugs (NSAIDs) and combination analgesics containing paracetamol, aspirin and caffeine.